Morphological and molecular phylogeny of Clinostomum sp. (Digenea: Clinostomidae) metacercariae, using DNA barcode from a South American freshwater fish - Gião, T. (2025)
Here, we present a comprehensive morphological and molecular phylogenetic analysis of Clinostomum sp. (Digenea: Clinostomidae) metacercariae parasitizing two freshwater fish species from Southeast Brazil: Serrasalmus spilopleura (piranha) and Callichthys callichthys (tambuatá). The morphological examination revealed distinct characteristics of metacercariae in each host. Using the cytochrome c oxidase I (COI) gene barcode region, we obtained DNA sequences that allowed for accurate phylogenetic placement. Phylogenetic analyses revealed that Clinostomum sp. HM41 (metacercariae), isolated from S. spilopleura, exhibited 86% similarity to Ithyoclinostomum yamagutii, while Clinostomum sp. HM125 (metacercariae), from C. callichthys, showed 98.7% similarity to Clinostomum sp. Cr_Ha1. The phylogenetic trees constructed through Bayesian Inference and Maximum Likelihood methods indicated high biodiversity within the Clinostomum genus and strong support for distinct lineages. These findings enhance our understanding of the diversity and ecological distribution of Clinostomum species in South American freshwater environments.